Chemical constituents and biological activity from the stem barks of Croton oblongifolius Roxb. from Amphoe Dan Sai, Loei province - Kullaphan Siriwat (Chulalongkorn University, 2007)
Thesis (M.Sc.)--Chulalongkorn University, 1999